Scalable Hierarchical‐Colored Passive Cooling Metapaint for Outdoor Facility - Maiping Yang; Zikang Zhou; Mingxiang Liu; Jiawei Wu; Jiaxin Li; Jun Liang; Shiliang Zhang; Mingyue Chen; Hongtao Zeng; Xiaofeng Li; Hao Han; Chong Hou; et al. (EcoMat)
ABSTRACT The temperature of metal‐based facilities rises significantly under high outdoor solar irradiation, leading to serious safety accidents. The application of active cooling technology poses challenges due to its high energy consumption, especially in complex outdoor environments. Passive cooling devices with high solar reflection and thermal emission can continuously cool objects under sunlight. However, the white or silvery passive cooling devices do not meet the need for aesthetics and specific demands. Here, we present a hierarchical metapaint for outdoor facilities that simultaneously achieve vibrant color and passive cooling ability. The top layer selectively absorbs visible wavelengths to display desired colors, while the underlayer boosts the reflection of near‐to‐short wavelength infrared (NSWIR) light to prevent solar heating. The metapaint‐coated metal is resistant to high and low temperatures, acidic and alkaline environments, and simulated seawater. It also has satisfactory anti‐fouling properties. When compared to metal coated without commercial paint, the hierarchical passive cooling paint (metapaint) coated metal can cool up to 9.7°C and 17.1°C. The metapaint has excellent passive cooling performance, attributed to its broad‐spectrum selective regulation function. Our work offers a simple, inexpensive, and scalable approach to reduce cooling energy usage and promote a low‐carbon lifestyle.